COVID-19 Impact on Teachers’ Organizational Commitment in Schools - Akartuna, Izlem Şerife Safkan; Serin, Oğuz (Frontiers in Psychology, 2022)
Highly committed teachers spend more effort helping their schools achieve the academic goals. The Covid-19 pandemic had a dire effect on education worldwide. However, just after a few semesters, teachers were asked to return back to schools to teach in person. This study aims to analyze the organizational commitment levels of school teachers before and after the implementation of the Covid-19 pandemic measures that resulted in a two semester break in face-to-face teaching. In this study, a quantitative research method was utilized. A total of 300 teachers’ commitment levels were assessed in a longitudinal test by using a popular tool in order to see the relative change as result of Covid-19 pandemic in Cyprus. The study mainly focuses on gender, marital status, education levels, job experience, and duration of work in the organizations in which the information from responses were statistically analyzed. According to the results of the quantitative analysis, the organizational commitment sampling average were determined to be at medium-high levels. The commitment levels of teachers were observed to decrease after the Covid-19 pandemic measures came to be implemented in schools. A detailed investigation of the school teachers’ commitment levels corresponding to the different demographic characteristics before Covid-19 and after the implementation of normalization measures is presented herein.